Characterization of diatomite, leonardite and pumice - Pookmanee P. (2017)
© 2016 Trans Tech Publications, Switzerland. This research studies compositions of diatomite, leonardite and pumice for utilization appropriate to the properties of materials. Chemical compositions of these materials were characterized by X–ray fluorescence spectrometry (XRF) and energy dispersive X–ray spectrometry (EDXS). The silica was major component of these materials. The morphology was investigated by scanning electron microscopy (SEM). Diatomite was cylindrical in shape, leonardite was sheet or flake in shape and pumicewas prismatic in shape. The structure was studied by X–ray diffraction (XRD). It was found that the mineral composition of diatomite, leonardite and pumice showed cristobalite low, quartz and anorthite, respectively. The functional groups were identified by Fourier transform infraredspectrometry (FTIR). The functional group of siloxane was obtained and dominated vibration in these materials. And the vibration of carboxylic, alcoholic and carbonyl groups were obtained in leonardite.